PERANAN MOTIVASI BERPRESTASI TERHADAP KOMPETENSI DAN KEPUASAN KERJA PEGAWAI - Suryadana, M. Liga (Majalah Bisnis & IPTEK, 2021)
The purpose of this study is to determine the effect of achievement motivation and competence toward employee satisfaction. The research method used survey method by using purposive sampling of the research object with a total population sample of 50 employees. Data were analyzed using structural equation modeling (PLS). Results showed that achievement motivation significant effect on the competence and employee satisfaction. Competence has significant effect on employee satisfaction. This indicates that the lack of attention to achievement motivation and competence will increase employee satisfaction. Keywords: achievement motivation; competence; employee satisfaction.